Hubungan Komunikasi Interpersonal Orang Tua dengan Perilaku Seksual Pranikah Remaja di Kota Padang - Nita Tri Putri; Djaswadi Dasuki; Budi Wahyuni (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: The phenomenon that is troubling many parties at the present time is the pattern of the adolescent courtship leading to sexual intercourse. Most teens consider premarital sexual behavior is normal and common. Interpersonal communication parents is not good to their children will cause conflicts that impact on adolescent premarital sexual behavior. By looking at the picture of interpersonal communication old man is expected to overcome adolescent premarital sexual behavior.Objektive : The purpose of this study was to determine the relationship between interpersonal communication of parents toward adolescent premarital sexual behavior.Method: This was an observational study using cross-sectional design and mixed methods approaches (quantitative and qualitative). The experiment was conducted at SMAN A, SMAN B, SMA C Idan MAN D Padang with research subjects totaling 299 teenagers. Informants for qualitative data that consists of 4 boys, 4 girls and 8 parents of the school to be studied.Results and Discussion: Indicates that there is a statistically significant relationship (p <0.05) between the independent variables (interpersonal communication of parents) with dependent variable (adolescent premarital sexual behavior) with a RP 3.71 95% CI (2.62 to 5.25). interpersonal communication of parents after the controlled variable peers, the media and religiosity there is also an increase of 49%.Conclusion: premarital sexual behavior in adolescents at risk because interpersonal communication of parents are not good . Other factors that affect the risk of premarital sexual behavior in adolescents are peers, the media and the level of religiosity. The results of in-depth interviews permissiveness and emotionally intimate relationship with parents also have an impact on the relationship is not good between parents and teenagers in interpersonal communication.Keywords: interpersonal communication of parents, adolescent premarital sexual behavior